Analisis Metakognisi Siswa Dalam Pemecahan Masalah Aritmatika Sosial Ditinjau Dari Perbedaan Gender(Pada Kelas Vii Smp Muhammadiyah 5 Surakarta Tahun Ajaran 2016/2017) - Khairunnisa, Rifda, Dra. Nining Setyaningsih, M.Si (2017)
This study aimed to describe the students metacognitive ability in social arithmetic problems solving of class VII were reviewed based on gender differences. The ability of metacognition in this study consisted of three stages: planning, monitoring, and evaluation. This research is a qualitative descriptive. The subjects of this study is four students taking from class VII F of SMP Muhammadiyah 5 Surakarta in 2016/2017 year of academic. The data collection technique using interviews, test, documentation, and observation. The validity of the data is using a method triangulation. Data analysis techniques used in this research is a reduce the data, presenting data and drawn conclusions (verification). The results of this study showed that 1.) the ability of metacognition not used by male students at the first and second problems. The subject 1 (B) does not meet the three stages in metacognition abilities, and the second problem, students only meet the planning stage, while the subject 2 (A) only meet the planning phase in the first and second problems. 2) the ability of etacognition has used by female at the first and second problems. It is because the students who is subjects 3 (E) and subject 4 (S) meets the three stages in metacognition abilities.Key word: Gender, Metacognition, Problem solving, Social Arithmethic